2013
DOI: 10.1038/bjc.2013.627
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and delayed effects of mammographic screening on breast cancer mortality and incidence in birth cohorts

Abstract: Background:Trend studies investigating the impact of mammographic screening usually display age-specific mortality and incidence rates over time, resulting in an underestimate of the benefit of screening, that is, mortality reduction, and an overestimate of its major harmful effect, that is, overdiagnosis. This study proposes a more appropriate way of analysing trends.Methods:Breast cancer mortality (1950–2009) and incidence data (1975–2009) were obtained from Statistics Netherlands, ‘Stg. Medische registratie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This study resulted in an overdiagnosis estimate of 11%, which is comparable with our overdiagnosis estimate of 10–17% at a period in time (result not presented), i.e ., 5‐year periods. A major strength of our study is, however, that we estimated overdiagnosis in birth cohorts, thereby estimating overdiagnosis from the increase in breast cancer incidence during screening and the drop in incidence after leaving screening in the same women and preventing overestimation of overdiagnosis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study resulted in an overdiagnosis estimate of 11%, which is comparable with our overdiagnosis estimate of 10–17% at a period in time (result not presented), i.e ., 5‐year periods. A major strength of our study is, however, that we estimated overdiagnosis in birth cohorts, thereby estimating overdiagnosis from the increase in breast cancer incidence during screening and the drop in incidence after leaving screening in the same women and preventing overestimation of overdiagnosis …”
Section: Discussionmentioning
confidence: 99%
“…Until now, such an APC‐model has been used only once to estimate overdiagnosis at a period in time . Overdiagnosis estimates at a period in time have, however, as major disadvantage that they do not study the increase in breast cancer incidence during screening and the drop in incidence after leaving screening in the same women thereby overestimating overdiagnosis . This disadvantage can be overcome by studying overdiagnosis in birth cohorts, i.e ., following the same women over time.…”
mentioning
confidence: 99%
“…Nonetheless, despite the lack of data on breast cancer incidence or hormonal therapy in our study population, our finding could contribute to explain, at least partially, the birth cohort effect on the increasing breast cancer incidence observed in the Netherlands across the 1938–1962 birth cohorts, as well as in the UK, Spain and France …”
Section: Discussionmentioning
confidence: 80%
“…Previous research on the Dutch screening program, which began in 1989, showed that uninvited cohorts experienced a continuous increase in mortality with age, while invited cohorts presented a diverging trend within five years after screening invitation. 27 Afterward, mortality rates started to rise again, although at a lower rate than in uninvited cohorts. 27 In Lithuania, the pattern of BC mortality is very similar to Estonia, showing a major decrease since 1996.…”
Section: Discussionmentioning
confidence: 97%